Imagining Italy : Victorian writers and travellers - Hollington, Michael; Waters, Catherine; Jordan, John O. (Cambridge Scholars Pub., 2010)
This book is a companion volume to Dickens and Italy, edited by Michael Hollington and Francesca Orestano, which aimed to fill an important gap in our understanding of England's paramount novelist by studying his personal, political and literary relation to the foreign country he loved best of all of those he visited. Its focus is wider and its scope more ambitious and speculative. Without in any way leaving Dickens or his writings about Italy behind, the attempt here is to approach the Victo ...